An Ethics-informed, Policy-based Approach to the Management of Challenges Posed by Living-at-Risk, Frequent Users of Emergency Departments - Kirby, Jeffrey; Nielsen, Lisbeth (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
The complex health and social circumstances of living-at-risk, frequent users of emergency departments (aREDFUs) in the health jurisdictions of high-income countries, and the related, significant challenges posed for emergency departments and the health care providers working within them, are identified and explored in the paper. Ethical analyses of a set of relevant domains are performed, i.e., individual and relational autonomy considerations, relevant social construction and personal responsibility conceptions, patient welfare principles (beneficence, nonmaleficence, continuity of care), harm reduction methodologies and their applications, health equity, and justice considerations of the distributive, formal and social types. The outcomes of these analyses demonstrate that there are ethically compelling reasons for emergency departments to adopt an ethics-informed, policy-based approach to the longitudinal care and management of living-at-risk, frequent users of emergency departments. From a formal justice perspective, the development and uses of such an approach are justified by a demonstrable relevant difference between living-at-risk, frequent users of emergency departments and other persons and groups of patients who visit emergency departments. We propose an example of such a policy-based approach. Examples of possible, pragmatic applications of this approach, which help ensure that aREDFUs who present to the ED are managed in a fair and optimally consistent manner, are provided for the consideration of an urban emergency department’s policymaking working group.